Färgen och landskapsarkitekturen - Hamberg, Maria (2012)
I gained my interest for color during my years at the landscape architect program. I felt that you as a student in design courses constantly were faced with the problems of coloration. A subject that I perceived to be difficult, especially for us students that lacked the experiences from how a project on the drawing board turns out when it finally is built. As a professional landscape architect you there have a greater experience but I wondered how much awareness about color you actually have as a professional. How does one think about coloration and how can you use color as a formative tool? And how does color truly affect us humans? Does color have significance for the experience of landscape architecture? The object with this project is to illustrate color and it’s place in landscape architecture. My goal is to raise the awareness for the relationship between color and the experience of the urban surroundings. To fulfill these objectives the project is based on three key issues: - How do you compose a good coloration? - Which is the role of coloration for the professional landscape architect in their designing work? - How does a changed coloration of a place change the experience of it? Part one – Background study The first part of the project consists of a theoretical study. Through literature the answer to the question how, in basic means, we humans are affected by the perception of color. The main source for this study is Fridell Anter & Enbergs book Utvändig färgsättning (1997). The reason behind that choice is the orientation it has towards the experience of color in urban environments that other literature was lacking. Part two – Meeting with three landscape architects In part two the question “which is the role of coloration for the professional landscape architect in their designing work?” is answered through interviews with three now professional landscape architects. Based on their projects three landscape architects where chosen; Åsa Drougge, Thorbjörn Andersson and Veronika Borg. Interviews where held with one and each of them about how they have used color in the selected project and how they looked upon color in their work in general. How they found the attitude towards color in the professional field where also discussed. Part three – Coloration of the Bysis plaza, Stockholm. In part three the Bysis plaza in Stockholm was selected as the place to through coloration explored the issue, “how does a changed coloration of a place change the experience of it?” Through photomontage in Photoshop the plazas current coloration were changed in three different ways that was chosen based on the result of the conclusions from the interviews in part 2. Perceived NCS-colors (explained in the background study) where measured out from the different colorations in order to find out the actual color tones. An analysis was performed of how the different coloration was perceived and the result was connected back to the NCS-colors and the theories that the background study showed. Part four – My own coloration In the fourth part the focus was on applying the result that had emerged during the project. Theories and ideas on how you compose a good coloration is concluded in a check-list. In order to get to try the theories a coloration through photomontage was made of the Luma park in Stockholm. Afterwards the check-list was revised.